Revolution-bump mapping with texture function adjustment according to the geometry of the revolved object - Ragragui, Anouar; Chahdi, Adnane Ouazzani; Arbah, Amina; El Moubtahij, Hicham; Halli, Akram; Satori, Khalid (Journal of graphic engineering and design, 2025)
Nowadays, 3D computer graphics are firmly anchored in our daily lives, extending across a multitude of distinct fields. Although each field follows its specific objectives, two major objectives are taken into consideration: realism and rendering speed. This is why image-based rendering (IBMR) techniques, such as revolution mapping, are gaining interest. Revolution-bump mapping is an image-based rendering that allows the creation of 3D objects in their entirety and without using polygonal meshes. The objective of the study presented in this paper is to improve the revolution-bump mapping technique as well as its extensions while ensuring that the application of textures on revolved surfaces is realized adequately. This development will allow the creation of pre-existing revolve models, while maintaining the essential rendering speed requirements for real-time rendering.